Efficacy of vonoprazan for the prevention of bleeding after gastric endoscopic submucosal dissection with continuous use of antiplatelet agents - Yoshii, Shunsuke; Yamada, Takuya; Yamaguchi, Shinjiro; Hayashi, Yoshito; Nakahara, Masanori; Shibukawa, Narihiro; Yamamoto, Masashi; Ishihara, Ryu; Kinoshita, Kazuo; Egawa, Satoshi; Tsujii, Yoshiki; Iijima, Hideki; Takehara, Tetsuo (Endoscopy International Open, 2020)
Background Post-procedural bleeding, after gastric endoscopic submucosal dissection (ESD) for high risk thromboembolic cases that require continuous antiplatelet therapy, is challenging. Its incidence rate is > 20 % among those using conventional antacids. We evaluated the efficacy of perioperative management with vonoprazan to prevent post-ESD bleeding.Materials and methods This was a multicenter prospective interventional trial conducted at 10 Japanese referral centers. Patients who regularly used antiplatelet agents (aspirin or thienopyridine derivatives, etc.) and who required continuous antithrombotic medication due to high thromboembolic risk were enrolled. They underwent gastric ESD with continuous aspirin therapy. Oral administration of vonoprazan (20 mg daily) was started from the day of ESD and continued for 28 days. The primary end point was the incidence of post-ESD bleeding. The sample size was 50 patients, and vonoprazan was considered to be effective when the upper threshold of the 95 % confidence interval (CI) for post-ESD bleeding did not exceed 20 %.Results Although 50 patients were enrolled, one patient withdrew consent. Therefore, 49 patients were included in the analysis. One patient who used aspirin and clopidogrel experienced bleeding 11 days after ESD. The overall post-ESD bleeding rate was 2.0 % (1/49; 95 %CI 0.4–10.7 %). Thromboembolic events were not observed. One case of ESD-associated adverse events (perforation) and one case of drug-associated adverse events (drug eruption, possibly due to vonoprazan) were observed.Conclusions Vonoprazan may be efficacious for preventing post-ESD bleeding in patients using continuous antiplatelet therapy, warranting further comparative study to definitively test the effectiveness of the drug.